The influence of service quality on customer satisfaction in maintaining loyalty at Coco SPBU in Medan City - Purba, Ines Adewinda; Surjasa, Dadang; Safitri, Dian Mardi (Universitas Mercu Buana, 2024)
Nowadays, more and more people use private vehicles, resulting in an increase in the number of vehicles and also fuel consumption. Customer satisfaction is one of the factors that influences customer loyalty. Customer loyalty is an indicator of success in making customers interested in using services or products again. The aim of this research is to determine the factors that influence service quality on customer satisfaction and loyalty at COCO gas stations in Medan City, North Sumatra. This research is quantitative research. The data analysis method used is Structural Equation Modeling-Partial Least Square (SEM-PLS) Smart PLS software version 4. The population in this study are customers at COCO gas stations in Medan City, North Sumatra. This research uses a questionnaire data collection technique with a sample of 100 respondents, which contains 18 indicator questions that can represent an assessment of gas station services. From this research, the results show that there is a significant influence on physical evidence and power on customer satisfaction, as well as customer satisfaction on customer loyalty.